INVESTIGATION OF EFFECTS ON FUEL CONSUMPTION AND EXHAUST EMISSIONS BY USING BIOETHANOL GASOLINE MIXTURE IN AN ENGINE WITH ULTRASONIC FUEL SYSTEM - Ozturk, Gokhan; Tanyeri, Burak; Oner, Cengiz (Vinca Inst Nuclear Sci, 2024)
This study compared the fuel consumption and exhaust emissions of a sparkignition engine using a carburetor fuel system, an injection fuel system, and an ultrasonic fuel system. When using gasoline only, the ultrasonic fuel system showed a 31% decrease in fuel consumption compared to the carburetor system and a 15% decrease compared to the injection system. When adding 10% bioethanol to the gasoline, fuel consumption increased in all three systems, with the ultrasonic system showing the largest increase of 10%. Exhaust emissions were also measured, and the ultrasonic system showed a significant decrease in CO, HC, and NO x compared to the carburetor and injection systems, with the largest decrease in CO emissions. The addition of bioethanol to the fuel resulted in reducing exhaust emission values in all three systems, with the ultrasonic system showing the largest decrease in CO and HC emissions compared to the carburetor and injection systems, but with an increase in NO x emissions compared to the injection system. When comparing three fuel systems, it was observed that injection fuel systems have the highest CO 2 values. Although the addition of alcohol to the fuel does not cause a significant change in CO 2 emission values for injection and ultrasonic fuel systems, an increase is observed in the carburetor fuel system. Overall, the ultrasonic fuel system showed promising results for reducing fuel consumption and improving exhaust emissions.
Keywords: ultrasonic fuel system; fuel injection system; alternative fuel; bioethanol